Investigation of awareness rate of prostate-specific antigen (PSA) among the general public in China and analysis of influencing factors - Wang, Yuqin; Xiao, Mukun; Zhang, Yueying; Hong, Zhiwei; Zhang, Ruochen; Xu, Qingjiang; Lin, Le; Wei, Yongbao (Frontiers in Public Health, 2023)
Objective: This study aimed to evaluate the awareness rate of prostate-specific antigen (PSA), and to provide scientific data information about prostate cancer (PCa) among the general public. Methods: A cross-sectional survey of PSA awareness was conducted in multiple regional populations using an online questionnaire. The questionnaire included the basic information, knowledge about PCa, the awareness rate and application of PSA, and future expectations towards the application of PSA screening in clinical practice. The study applied the methods of Pearson chi-square analysis and Logistic regression analysis. Results: A total of 493 valid questionnaires were included. 187 (37.9%) of the respondents were aware of PSA and 306 (62.1%) of the respondents were unaware of PSA. Statistically significant differences were obtained between the two groups in terms of different age, different work (learning) status, different occupations, different departments, and different habits of knowing medical knowledge (all p<0.05). The differences between the two groups in terms of whether they had been exposed to PSA screening and whether they had exposure to PCa patients or related knowledge were also observed (all p<0.05). Age ≥30 years, work (learning) related to healthcare, have the habit of understanding medical knowledge, exposure to PCa patients or related knowledge, exposure to PSA screening, and status as a graduate student and above were independent factors for the occurrence of PSA awareness events (all p<0.05). Age≥ 30 years, work (study) related to healthcare, and being aware of PSA were independent factors for the occurrence of future expectations towards PSA (all p<0.05). Conclusions: We firstly analyzed the public awareness of PSA. Different groups of people have different degrees of PSA or PCa awareness. We should designate corresponding popular science propaganda for different groups of people to increase the awareness rate of PSA.